Arbitrary Modeling of TSVs for 3D Integrated Circuits - Salah, Khaled; Ismail, Yehea; El-Rouby, Alaa (Analog Circuits and Signal Processing,, 2015)
This book presents a wide-band and technology independent, SPICE-compatible RLC model for through-silicon vias (TSVs) in 3D integrated circuits. This model accounts for a variety of effects, including skin effect, depletion capacitance, and nearby contact effects.  Readers will benefit from in-depth coverage of concepts and technology such as 3D integration, Macro modeling, dimensional analysis, and compact modeling, as well as closed form equations for the through silicon via parasitics. Concepts covered are demonstrated by using TSVs in applications such as a spiral inductor,  and inductive-based communication system, and bandpass filtering. ·Introduces a robust model that captures accurately all the loss modes of a TSV,  coupling parasitics between TSVs and the TSV nonlinear capacitance and resistance of the depletion region; ·Enables readers to use a model which is technology dependent and can be used for any TSV configuration; ·Reveals a novel on-chip wireless communication technique, based on TSV spiral inductors; ·Equips readers for fast parasitic extraction of TSVs for 3D IC design.